Nutritional status of children under six and socio-economic and demographic characterisitcs of households in the coastal barangays in Anini-y, Antique. - Garcia, Leonalyn E. (2010.)
This paper was designed to assess the nutritional status of children under six (0-71 months) and the socio-demographic and economic characteristics of their households in the coastal barangays in Anini-y, Antique. Data were gathered through face-to-face interview with household heads using an interview schedule. 168 household heads interviewed provided 259 children under six. The data were organized and summarized using frequency and percentages. The prevalence of malnutrition in terms of weight-for-age were the following: 32% were below normal and 1% were above normal. In terms of height-for-age, 46% were short or stunted and 0.4% were tall. A Multivariate Logistic Regression Analysis was employed so as to determine if there is a significant relationship between nutritional status of children under six with selected socio-economic and demographic factors. Multivariate analysis showed that the age of the child (5% level of significance), household income (10% level of significance), and experience of hunger (10% level of significance) had significant effect on the nutritional status of children under six s measured by weight-for-age. The model correctly predicts the true outcome at 69.11%. age of the child, household size, and household income were found to have significant effect at 1% level on the nutritional status of children under six as measured by height-for-age. In addition, age of the household head and the presence of vegetable garden were significant at 5% level of significance. The model was able to correctly predict 68.34% of true outcome.
Thesis (Undergraduated, Bachelor of Arts in Economics) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2010.
Keywords: Children -- Coastal Barangagys -- Anini-y, Antique -- Research